Comparison of Fig Juice Fruitghurt with Variations in Sucrose and Length of Fermentation - Anna Yuliana; Zalfa Zahira Fauziah; Hendy Suhendy (JURNAL SAINS NATURAL, 2023)
Fruitghurt is a fermented product made from fruit juice and milk, which is an important food source of protein to meet nutritional needs. Therefore, researchers added figs containing glucose, fructose, dietary fiber, and antibacterial properties to get the best fruit yoghurt. This study aims to determine the effect of sucrose concentration and the length of fermentation time for fig juice fruitghurt using Lactobacillus bulgaricus and Streptococcus thermophilus starters and to determine the antibacterial activity of fruit juice and fruitghurt through testing against Escherichia coli. Concentration was 0, 14, and 18%, and fermentation was carried out for 0, 18, and 24 hours, The parameters of this research were based on microbiological, chemical, and physical properties. The research showed that sucrose concentration and fermentation time affected Lactic Acid Bacteria (LAB), pH, , pH decreased from 4.5 to 4.0Total Titrated Acid (TAT), viscosity, total dissolved solids, color, aroma, texture, and taste. Total BAL had the highest value of  CFU/mL, and TAT increased from 0.50% to 0.65%. The viscosity with the highest value is 12.33 cP. Total dissolved solids decreased from 13% to 11%. All parameters meet the requirements of SNI 2981:2009. The antibacterial activity test showed an inhibition zone with a value of 7.4 mm. The average value of the researcher's preference for color, taste, and aroma in the 0-hour formula with 0% sucrose, the 24-hour formula with 14% sucrose, and the 24-hour formula with 18% sucrose. The best fermentation time and sucrose concentration was 24 hours and 18% sucrose.